Analisis Kompetensi Guru Berbasis Uji Kompetensi Guru (UKG) Pada Guru Sekolah Menengah Kejuruan (SMK) Bidang Keahlian Administrasi Perkantoran Di Surakarta Tahun Ajaran 2015 / 2016 - Farida Retno Wardhani (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2017)
This aim of this study is to determine: (1) The description of the teacher competence, especially pedagogical competence and professional competence of vocational high school teacher of office adminstration area of expertise in Surakarta who have followed UKG; (2) Obstacles the vocational high school teacher of Office Administration area of expertise encounter in Surakarta in taking UKG; (3) Type of education and training required by vocational high school teachers of Office Administration areas of expertise in Surakarta getting results UKG below the standards to improve the teachers professionalism. The method used in this study is qualitative research with case study approach. The sources of the data are primary data source in the form of words of informants and secondary data sources in the form of documentation and the archives of UKG results year 2015. The sampling techniques used purposive sampling and snowball sampling. Data collection techniques used are observation, interviews, and questionnaires. Based on the results of this study can be concluded that: (1) Pedagogical and professional competence of vocational high school teachers of office administration areas of expertise in Surakarta own good but still needs to be improved. It is seen from (a) The pedagogic and professional competence have been implemented as indicators Permendiknas No. 16 year 2007 (b) the average value of UKG on pedagogical competence is 51.13 and professional competence is 58.32 (c) The average value of competence pedagogic through questionnaires by 78.35 and amounted to 72.73 of professional competence. (2) Obstacles encountered in taking the UKG is the material tested on the professional competence is too broad, the lack of mastery of pedagogic competence, lack of mastery of the computer (3) Training required by vocational high school teachers of Office Administration areas of experties in Surakarta getting results UKG below the standard to improve the professionalism of teachers including in-depth training of administration productive office subject, training of pedagogical competence and professional competence gradually, computer training.